PERAN AYAH KRISTEN DALAM PEMENUHAN MISI KRISTUS DALAM KONTEKS KELUARGA - Tameon, Sance Mariana (Phronesis: Jurnal Teologi dan Misi, 2024)
According to God, fathers must guide their families with selfless love. If children correctly understand their earthly or physical father, they will also understand God well. In addition to being a follower of Christ, the parent must exhibit godly qualities and show him patience, humility, self-control, compassion, and meekness toward his children. Nonetheless, it is undeniable that many families are going through a crisis in the twenty-first century and lack the psychological and physical presence of a father. Many children are growing up without their fathers there. This study employs a descriptive methodology and a qualitative approach. The study aims to determine how Christian fathers contribute to the family's fulfillment of Christ's mission. The study's findings indicate that Christian fathers have fulfilled three functions: serving as loving fathers, role models, and spiritual leaders for their family members.